Interphase chromatin of the peripheral blood cells of patients with a chronic form of myeloid leukemia (Ph+) - Iudina, I E; Fedorova, K N (Biulleten' eksperimental'noi biologii i meditsiny, 1984)
It was shown with labeled AO cytofluorometry using the authors' modification of DNP cell thermal denaturation that in untreated patients with chronic myeloid leukemia (CML) in the blast crisis phase, the melting profiles of peripheral blood cell chromatin were "unclassified", strictly individual in nature (unlike the identical parameter in healthy subjects) that may attest to regulatory disturbances of the genetic apparatus. The demonstration of the "normalization" of the melting profiles of chromatin in CML patients during the clinico-hematological compensation of the disease makes it possible to suggest that luminescent fluorometry (in the authors' modification of DNP cell thermal denaturation) should be used for the treatment of hemoblastoses in order to study the genesis and time-course of the diseases running their course with remissions and as criterion of drug therapy of these diseases.